2005
DOI: 10.1159/000087007
|View full text |Cite
|
Sign up to set email alerts
|

Neocuproine, a Copper (I) Chelator, Potentiates Purinergic Component of Vas Deferens Contractions Elicited by Electrical Field Stimulation

Abstract: Effects of the specific copper (I) chelator, neocuproine, on the purinergic and adrenergic components of nerve-evoked contractions were investigated in the prostatic rat vas deferens. Electrical field stimulation (EFS; 4 Hz) induced bimodal contractions of vas deferens tissue in the presence of α1-adrenoceptor antagonist prazosin (to isolate the purinergic component) or purinoceptor antagonist suramin (to isolate the adrenergic component). Neocuproine significantly potentiated the purinergic compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(33 reference statements)
3
2
0
Order By: Relevance
“…Decrease on the SC-induced by NC but not cuprizone indicated that a copper(I)-sensitive mechanism may play a role in the inhibitor effect of NC in the mouse bladder. The activity/inactivity of copper chelators are in agreement with our previous studies conducted on rat bladder and vas deferens (17,19). However in the rat urinary bladder, L-NOARG, a nitric oxide synthase inhibitor, had no effect on the facilitator effect of NC on nerve-evoked contractions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Decrease on the SC-induced by NC but not cuprizone indicated that a copper(I)-sensitive mechanism may play a role in the inhibitor effect of NC in the mouse bladder. The activity/inactivity of copper chelators are in agreement with our previous studies conducted on rat bladder and vas deferens (17,19). However in the rat urinary bladder, L-NOARG, a nitric oxide synthase inhibitor, had no effect on the facilitator effect of NC on nerve-evoked contractions.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous studies showed that the chelation of endogenous copper(I) caused an enhancement on the spontaneous activity in some of rat tissues such as bladder and vas deferens tissues of rats and pregnant rat myometrium (16)(17)(18)(19) and the involvement of purinergic receptors and/or Ca 2+ levels in those responses. In the present study, our aim was to evaluate whether the contribution of purinergic pathways and/or intracellular calcium levels in the effects of neocuproine in the mouse bladder tissues are similar to rat tissues or not.…”
Section: Introductionmentioning
confidence: 99%
“…The excitatory effect was significantly inhibited by suramin, a purinergic receptor antagonist. These results are consistent with the previous studies in rat bladder and vas deferens tissues and the results have been suggested that NC-induced excitatory effects may be owing to the activation of the purinergic excitatory responses (Gocmen et al, 2004(Gocmen et al, , 2005. In contrast to the response of rat bladder, NC caused recurrent and reversible inhibition on spontaneous contractions and basal tonus on in vitro isolated mouse bladder strips and whole bladder tissue.…”
Section: Discussionsupporting
confidence: 93%
“…The inhibitor effect did not occur in the presence of pre-prepared NC-Cu(I) complex. The results indicate that a copper (I)-sensitive mechanism may play a role in the inhibition effect of NC on purinergic responses of mouse bladder tissue, and previous studies of Gocmen et al, 2004 and support that the copper(1)-sensitive mechanism may play a role by facilitating purinergic excitatory response (Gocmen et al, 2004(Gocmen et al, , 2005. In addition, it has been suggested that NO releases with S-nitrosothiols, a sulfhydryl-containing compound, and NC affect the responses of S-nitrosothiols by its ability to chelate copper in the bladder (De Man et al, 1999), however, it was exhibited that it is different from L-NOARG mechanism, because of that NOS inhibitor, L-NOARG did not change the effect of NC responses (Gocmen et al, 2004).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation